Access and use of sexual and reproductive health services among asylum-seeking and refugee women in high-income countries: A scoping review. - Emma Stirling-Cameron; Salma Almukhaini; Justine Dol; Benjamin J DuPlessis; Kathryn Stone; Megan Aston; Shira M Goldenberg (PLoS ONE)
Background Refugee and asylum-seeking women are known to experience a myriad of intersecting sociocultural, institutional, and systemic barriers when accessing healthcare services after resettlement in high-income countries. Barriers can negatively affect service uptake and engagement, contributing to health inequities and forgone care. Access to sexual and reproductive healthcare (e.g., family planning, cervical cancer prevention) has largely been understudied. This scoping review sought to: i) examine the use of sexual and reproductive health services among refugee and asylum-seeking women in high-income countries; and ii) identify barriers and facilitators influencing access to sexual and reproductive healthcare for refugee and asylum-seeking women in high-income countries. Methods This review was conducted in accordance with Joanna Briggs Institute Methodology for Scoping Reviews. Ten databases (e.g., CINAHL, MEDLINE, Embase) were searched for qualitative, quantitative, mixed method studies, and gray literature published anytime before February 2024 across high-income countries (defined by the World Bank). The Health Behaviour Model was used to examine and understand factors influencing service use and access. Results 3,997 titles and abstracts were screened, with 66 empirical studies included. Most were conducted in the United States (44%), Australia (25%), Europe (18%) and elsewhere and were qualitative (68%). Papers largely addressed contraception, abortion, cervical cancer screening, gender-based violence, and sexual health education. Included studies indicated that refugee and asylum-seeking women in high-income countries face a greater unmet need for contraception, higher use of abortion care, and lower engagement with cervical cancer screening, all when compared to women born in the resettlement country. Frequently reported barriers included differences in health literacy, shame and stigma around sexual health, language and communication challenges, racial or xenophobic interactions with healthcare providers, and healthcare/medication costs. Conclusions Studies across the globe identified consistent empirical evidence demonstrating health inequities facing refugee and asylum-seeking and myriad intersecting barriers contributing to underuse of essential sexual and reproductive health services. Facilitators included multilingual healthcare provider, use of interpreters and interpretation services, community health promotion work shops, and financial aid/Medicare.